RETRACTED: Amorphous Selenium Nanoparticles Improve Vascular Function in Rats With Chronic Isocarbophos Poisoning via Inhibiting the Apoptosis of Vascular Endothelial Cells - Zhu, Moli; Gao, Zhitao; Fu, Yutian; Qiu, Yue; Huang, Keke; Zhu, Chaonan; Wu, Yinan; Zhu, Tiantian; Wang, Qianqian; Yang, Lin; Yin, Yaling; Li, Peng (Frontiers in Bioengineering and Biotechnology, 2021)
Aim This study aimed to investigate the preventive effect and possible mechanism of amorphous selenium nanoparticles (A-SeQDs) on isocarbophos induced vascular dysfunction. Methods A-SeQDs was made by auto redox decomposition of selenosulfate precursor. Male rats were given isocarbophos (0.5 mg/kg/2 days) by intragastric administration for 16 weeks to induce vascular dysfunction. During the course, A-SeQDs (50 mg/kg/day) was added to the water from week 5. Then, the rats were killed to observe and test the influence of A-SeQDs on the vascular dysfunction induced by isocarbophos. Finally, human umbilical vein endothelial cells (HUVECs) were treated with 10% DMEM of isocarbophos (100 μM) for 5 days to detect the related indexes. Before the use of isocarbophos treatment, different drugs were given. Results A-SeQDs could reduce total carbon dioxide, MDA, VCAM-1, ICAM-1, IL-1, and IL-6 while increasing oxygen saturation, NO content, and SOD activity in rats. A-SeQDs also resulted in relatively normal vascular morphology, and the expression of sodium hydrogen exchanger 1 (NHE1) and caspase-3 decreased in rats. Furthermore, in HUVECs treated with isocarbophos, A-SeQDs maintained mitochondrial membrane potential, inhibited the cleaved caspase-3 expression, and released cytochrome c from mitochondria to cytosol. Conclusion A-SeQDs can inhibit the apoptosis of HUVECs through the mitochondrial pathway, and effectively treat the impairment of vascular endothelial function caused by isocarbophos, which is NHE1-dependent.